2016
DOI: 10.1111/anu.12424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritive value of fermented de-oiled physic nut,Jatropha curcas,seed meal for Nile tilapiaOreochromis niloticusfingerlings

Abstract: Jatropha curcas seed meal was fermented with Bacillus licheniformis (LFJSM) and Bacillus pumilus (PFJSM) separately using the solid-state fermentation. After fermentation, the crude protein and the total hydrolysed amino acid contents were increased in LFJSM and PFJSM, while fibre content, phytic acid, trypsin inhibitor and saponins were decreased. An 84-day feeding experiment was designed for the nutritional evaluation of LFJSM and PFJSM in Nile tilapia. Seven isonitrogenous (305.47 g kg À1 crude protein) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 51 publications
5
16
0
1
Order By: Relevance
“…However, Liu et al (2018) found that diets for rainbow trout containing CSM supplemented with 600 mg kg -1 protease achieved the minimum serum level of ALT and AST activities. These serum biochemical indices are usually employed to assess the nutritional and health status of fish (Hassaan et al, 2017). The increase rate of anabolic processes in fish may be due to increases in serum protein level to meet increased metabolic demands in fast growing fish, and the cyclic nature of the total serum protein is an indicator of the changes taking place in the serum globulin fraction (Helmy et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Liu et al (2018) found that diets for rainbow trout containing CSM supplemented with 600 mg kg -1 protease achieved the minimum serum level of ALT and AST activities. These serum biochemical indices are usually employed to assess the nutritional and health status of fish (Hassaan et al, 2017). The increase rate of anabolic processes in fish may be due to increases in serum protein level to meet increased metabolic demands in fast growing fish, and the cyclic nature of the total serum protein is an indicator of the changes taking place in the serum globulin fraction (Helmy et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Plant proteins might thus be considered as the most viable alternative in this respect for economic fish production in most of the developing countries (Kumar et al, 2011a;Kader et al, 2012;Hassaan et al, 2018). In this manner, it has become an inevitable trend of replacing fish meal with less expensive and locally available plant protein sources (Hassaan et al, 2017;Hassaan et al, 2018). Cotton seed meal (CSM) has been investigated as a potential alternative ingredient to both fish meal and soybean meal due to its cheaper cost, being readily available in some countries, particularly in the USA, China, India and Egypt, although the protein content can be variable (23-53%) depending on how this product is processed (Mbahinzireki et al, 2001;Yue and Zhou 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the success of commercial aquaculture production by reducing the cost of prepared diet, without reducing fish performance, leads to a positive impact on the profitability of commercial fish production (, & Lee). Recently (Hassaan, Goda, & Kumar, ; Hassaan, Soltan et al, ; Kumar et al, ) observed that the use of plant feedstuffs (such as wheat gluten, sunflower meal, soybean meal or soy protein concentrate) imposes some concerns due to the “food–feed competition,” rising prices, and carbon footprint involved in their production and importation. Thus, there is an increasing need to seek alternatives, particularly underutilized commodities, such as by‐products obtained from food, fermentation and pharmaceutical industries, rather than being highly dependent of imported plant feedstuffs, such as soybean meals, for aquafeeds formulation (Matos, Dias, Dinis, & Silva, ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that the high level of sunflower meal SFM 3 and un‐supplemented with xylanase recorded the lowest activity of all digestive enzymes. This decreased was attributed to the presence of antinutritional factors, high levels of fibre and NSP in SFM which reduced the digestion (Hassaan et al, ; Refstie, Storebakken, & Roem, ). On the other hand, addition of 3,750 U/kg xylanase increased the activities of chymotrypsin, trypsin, lipase, amylase and alkaline phosphatase in the intestine of O. niloticus .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, plant protein and their by-products are a suitable strategy to increase the sustainability of aquaculture production by reducing feed costs as well as reducing the environmental adverse impact (Tacon & Metian, 2015). Several alternative plant protein sources in tilapia diets have been investigated in recent years due to the reduction in fish meal production and increasing its cost, such as cotton seed meal (El-Saidy & Gaber, 2004), okara meal (El-Saidy, 2011), fermented soybean meal (Hassaan, Soltan, & Abdel-Moez, 2015), soy protein concentrate (Ribeiro, Vidotti, Ferreira, & Gonçalves, 2016), Jatropha meal (Hassaan, Goda, & Kumar, 2017), corn protein concentrate (Khalifa, Belal, El-Tarabily, Tariq, & Kassab, 2018) and fermented sunflower meal (Hassaan et al, 2018), which were showed to be suitable as partial replacements for fish meal. However, total replacement of fish meal with plant proteins has generally resulted in decrease in fish growth performance and feed utilization.…”
Section: Introductionmentioning
confidence: 99%